Hemophagocytic lymphohistiocytosis (HLH) presenting as fever of unknown origin and acute liver failure. (2018) - Lutfi, Forat; Patel, Arpan; Becker, Dawn; Shahid, Mohammad; Shah, Kairav
Abstract: A 51-year-old previously healthy woman presenting with two-weeks of fever, flu-like symptoms, jaundice, and abdominal pain was found to have pancytopenia, transaminitis, and significantly elevated ferritin in the setting of an Epstein-Barr Virus (EBV) infection. Bone marrow biopsy revealed phagocytic macrophages consistent with findings of hemophagocytic lymphohistiocytosis (HLH). Given bone marrow findings and that the patient had five of the eight clinical criteria supporting the diagnosis of HLH, chemotherapy was initiated as per the HLH-94 protocol with initial improvement in patient's symptoms and overall functional status. This case demonstrates a classic presentation of HLH and displays the importance of correct diagnosis and prompt treatment.